2021
DOI: 10.1186/s12891-021-04644-4
|View full text |Cite
|
Sign up to set email alerts
|

Total wrist arthrodesis with and without arthrodesis of the carpoMetacarpal joint (WAWWAM): study protocol

Abstract: Background It is controversial whether or not the carpometacarpal joint (CMCJ) should be included in total wrist arthrodesis (TWA). Complications commonly occur at this site and studies examining its inclusion and exclusion are conflicting. A randomised clinical trial comparing wrist arthrodesis with CMCJ arthrodesis and spanning plate to wrist arthrodesis with CMCJ preservation and non-CMCJ spanning plate has not been performed. Method A single ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 15 publications
0
5
0
1
Order By: Relevance
“…69 Conservar la movilidad carpometacarpiana en el contexto de una artrodesis total puede mejorar la fuerza de agarre y de hacer el puño, mientras que, como contrapartida, puede producirse hipermovilidad y dolor por sobrecarga de dicha articulación en una muñeca fusionada. 70 A su vez, existe división en relación con la posición que debe adoptar la mano. Normalmente, se coloca la muñeca en ligera dorsiflexión y desviación cubital para optimizar el poder de agarre.…”
Section: Artrodesis Radiocarpiana Totalunclassified
See 1 more Smart Citation
“…69 Conservar la movilidad carpometacarpiana en el contexto de una artrodesis total puede mejorar la fuerza de agarre y de hacer el puño, mientras que, como contrapartida, puede producirse hipermovilidad y dolor por sobrecarga de dicha articulación en una muñeca fusionada. 70 A su vez, existe división en relación con la posición que debe adoptar la mano. Normalmente, se coloca la muñeca en ligera dorsiflexión y desviación cubital para optimizar el poder de agarre.…”
Section: Artrodesis Radiocarpiana Totalunclassified
“…69 Preserving carpometacarpal mobility in the context of total arthrodesis can improve grip strength and fist-making ability, but on the flip side, it can lead to hypermobility and pain due to overloading of this joint in a fused wrist. 70 Additionally, there is a division regarding the position the hand should adopt. Typically, the wrist is placed in slight dorsiflexion and ulnar deviation to optimize grip power.…”
Section: Total Radiocarpal Arthrodesismentioning
confidence: 99%
“…We feel that this is a minor limitation given wrist arthrodeses are reported to unite at approximately 12 weeks, and it is generally accepted that pain and function stabilize by 12 months. 14 In addition, published literature suggests that most long-term complications, such as metalware failure or nonunion, occur with a 2-year initial period after which there is long-term satisfaction with the procedure. 14,15 All patients enrolled in this study showed signs of union, and therefore, the authors continue to monitor patients to understand the functional profile of these plates.…”
Section: Limitationsmentioning
confidence: 99%
“…14 In addition, published literature suggests that most long-term complications, such as metalware failure or nonunion, occur with a 2-year initial period after which there is long-term satisfaction with the procedure. 14,15 All patients enrolled in this study showed signs of union, and therefore, the authors continue to monitor patients to understand the functional profile of these plates. The authors also acknowledge that another limitation of this study was a lack of preoperative data, specifically for functional assessment and pain scores, although this is in keeping with another comparable study.…”
Section: Limitationsmentioning
confidence: 99%
See 1 more Smart Citation